Playbook for the design and implementation of food systems-focused accelerator programs in Africa - Hauke, Dahl; Peterson, Nathanial; Nguvi, Caroline (2024)
Africa’s food systems face the dual challenge of addressing climate change and feeding a rapidly growing population. Small-scale farmers, pivotal to African agriculture, struggle with limited access to climate-smart agriculture (CSA) practices and climate information services (CIS). Agribusinesses can bridge this gap by bundling CSA solutions with products and services, leveraging their networks to scale innovations. This playbook offers a comprehensive framework for designing climate-smart accelerators, emphasizing market alignment, financial sustainability, and capacity building. By fostering innovation and investment, the playbook aims to transform Africa’s food systems into resilient, sustainable, and equitable ecosystems capable of meeting future demands.